THE INFLUENCE OF FINANCIAL DISTRESS, CASH HOLDINGS, AND PROFITABILITY TOWARD EARNINGS MANAGEMENT WITH INTERNAL CONTROL AS A MODERATING VARIABLE: THE CASE OF LISTED COMPANIES IN ASEAN COUNTRIES - Putri, Maya; Ary Binsar Naibaho, Eduard (Jurnal Akuntansi dan Keuangan Indonesia, 2022)
This study aims to define and analyze the relationship between financial distress, cash holding, and profitability and earnings management with internal control as a moderating variable in relation to six major countries in Southeast Asia (Indonesia, Malaysia, Singapore, Thailand, Philippines, and Vietnam). Earnings management is measured by the Jones model of discretionary accruals. Secondary data sources are used, namely companies listed on the S&P Capital IQ, with 480 observations that fit the criteria. Purposive sampling techniques are employed, with a new sample of observational data from the consumer staples sectors in the six countries covering the period 2016-2020. ASEAN was chosen because of the lack of previous research using this as the research population. The data were processed using the Eviews 11 program. The theoretical basis used in the research is agency theory and signaling theory. The results indicate that financial distress and profitability positively affect earnings management, whereas cash holdings have a negative impact. The study also verifies that internal control as a moderating variable strengthens the negative impact of financial distress and profitability on earnings management, while strengthening the positive impact of cash holdings.